POST SOCIAL CONFLICT MANAGEMENT IN SOUTH LAMPUNG (STUDIES IN LAMPUNG REGIONAL POLICE) - Saputro Prayitno (Cepalo, 2019)
The clash between Balinuraga Village and Agom Village was caused by sexual harassment where there was a slander to the Balinese by the Lampung people. The issues raised are the factors that cause social conflict, efforts to handle and inhibiting factors from the Police, Local Government and Community Leaders / Customary Leaders / Religious Leaders in handling post-conflict conflicts in Lampung as an effort to provide legality. legal certainty and protection for the wider community, especially people in South Lampung. This study aims to determine the causes of conflict, post-conflict handling of social conflict in South Lampung society and inhibition of post-conflict handling in social conflict in South Lampung society. This type of research is analytical descriptive research using the approach of normative legal problems (library research). This study uses secondary data in the form of secondary legal materials, the books of legal experts. The results show that there are reasons that can cause social conflict in South Lampung, such as lack of work; Unresolved conflict; Social inequality factor; Lack of communication that causes confusion in the certainty of a news; There are those who want a split between the two villages. Post-conflict handling is carried out by the Regional Government, Lampung Regional Police and Community Leaders / Customary Leaders / Religious Leaders together through reconciliation, rehabilitation and reconstruction efforts, then counseling and spreading the need for people who are aware of the law and harmony society, to create a community that is orderly, and peaceful.   The conclusion of this study is that the Police, Local Government assisted by the community (religious leaders, traditional leaders and community leaders) must make a planned, integrated, sustainable and measurable post-conflict recovery effort through reconciliation, rehabilitation and reconstruction efforts. Law Number 7 of 2012 concerning Management of Social Conflicts also regulates the role of the community, and funds the handling of conflicts, so that the community is aware of the law and harmony in society, orderly, and peaceful.